Social housing in Spain: obsolescence and intervention strategies - Concepción López González (Vitruvio: International Journal of Architectural Technology and Sustainability)
Social housing in Spain has its origin in the first Cheap Houses Law that was promulgated in 1911, trying to provide a solution to a housing need for the working class who flocked to the cities in waves of migration from rural areas. Since then, legislative initiatives have been taking place to mitigate the housing problem. Each one of them was contributing elements that presumably contributed to the hygiene and habitability of the house without forgetting the economic conditions. At the moment, in Spain there is a large real estate park inherited from these initiatives. In many cases, these are neighborhoods that currently show notable energy and social vulnerability. Aware of the need to adapt these homes to the regulatory requirements related to energy efficiency, comfort and the physical and technical characteristics of the construction, the Research Centers are developing multiple investigations aimed at favoring the adaptability of homes and improving the quality of life of its inhabitants. This article takes a tour of the evolution that social housing has had during the 20th century in Spain and the current state of research aimed at adapting it to the new energy, habitability and sustainability requirements.